1998
DOI: 10.1111/j.1600-0625.1998.tb00295.x-i1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional aspects of the hairless (hr) gene in laboratory rodents and humans

Abstract: and susceptibility to dioxin toxicity. On the basis of our current understande-mail: amc65/columbia.edu ing of hairlessness, we speculate on the putative functions of the hr gene product in skin physiology, and particularly, in hair follicle biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 113 publications
(205 reference statements)
4
73
1
2
Order By: Relevance
“…Mutations of the human hairless gene revealed congenital hair loss disorders. Some mutant alleles in both mice and humans show skin wrinkling and papular rash (Panteleyev et al, 1998). Hairless null KO mice show both hair and skin phenotypes (Zarach et al, 2004).…”
Section: Hairlessmentioning
confidence: 99%
“…Mutations of the human hairless gene revealed congenital hair loss disorders. Some mutant alleles in both mice and humans show skin wrinkling and papular rash (Panteleyev et al, 1998). Hairless null KO mice show both hair and skin phenotypes (Zarach et al, 2004).…”
Section: Hairlessmentioning
confidence: 99%
“…Recent studies have suggested that HR protein acts as a nuclear receptor co-repressor in concert with the vitamin D receptor gene and represses the expression of WISE protein, which inhibits Wnt signaling 16,17 . The follicular cysts seen in APL patients may arise from follicular remnants that survive after the follicle breaks apart during catagen 13,18 . As the cyst epithelium expresses keratin K17, which normally occurs in the outer root sheath of hair follicles, cysts in APL patients appear to arise from the bulge of the hair follicle 13,19 .…”
Section: Discussionmentioning
confidence: 99%
“…the nu/nu and +/+ embryos thus selected were first subjected to He staining. the He stained sagittal sections of the embryos revealed that the nu/nu embryos contained no thymus, which is a feature of nu/nu mice [9], whereas the +/+ embryos presented a normal tissues pattern (Fig. 6).…”
Section: Metal Staining Condition In Micro-ct Analysismentioning
confidence: 95%